2018
DOI: 10.1371/journal.ppat.1006980
|View full text |Cite
|
Sign up to set email alerts
|

Viral targeting of TFIIB impairs de novo polymerase II recruitment and affects antiviral immunity

Abstract: Viruses have evolved a plethora of mechanisms to target host antiviral responses. Here, we propose a yet uncharacterized mechanism of immune regulation by the orthomyxovirus Thogoto virus (THOV) ML protein through engaging general transcription factor TFIIB. ML generates a TFIIB depleted nuclear environment by re-localizing it into the cytoplasm. Although a broad effect on gene expression would be anticipated, ML expression, delivery of an ML-derived functional domain or experimental depletion of TFIIB only le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 87 publications
2
25
0
Order By: Relevance
“…HCT intersections for nodes originally characterized as having a general role in RNA Pol II transcription, including TBP (q-values: SARS1, 2e-10; SARS2, 6e-23; MERS, 3e-16), GTF2B/TFIIB (q-values: SARS1, 7e-10; SARS2, 3e-23; MERS, 9e-14) and GTF2F1 (qvalues: SARS1, 2e-4; SARS2, 2e-13; MERS, 5e-5) were strong across all CoVs, and particularly noteworthy in the case of SARS2. In the case of GTF2B, these data are consistent with previous evidence identifying it as a specific target for orthomyxovirus 41 , and the herpes simplex 42 and hepatitis B 43 viruses. Moreover, a proteomic analysis that appeared in BioRXiv while this paper was under review identified a high confidence interaction between GTF2F2 and the SARS2 NSP9 replicase 32 .…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Trasupporting
confidence: 90%
“…HCT intersections for nodes originally characterized as having a general role in RNA Pol II transcription, including TBP (q-values: SARS1, 2e-10; SARS2, 6e-23; MERS, 3e-16), GTF2B/TFIIB (q-values: SARS1, 7e-10; SARS2, 3e-23; MERS, 9e-14) and GTF2F1 (qvalues: SARS1, 2e-4; SARS2, 2e-13; MERS, 5e-5) were strong across all CoVs, and particularly noteworthy in the case of SARS2. In the case of GTF2B, these data are consistent with previous evidence identifying it as a specific target for orthomyxovirus 41 , and the herpes simplex 42 and hepatitis B 43 viruses. Moreover, a proteomic analysis that appeared in BioRXiv while this paper was under review identified a high confidence interaction between GTF2F2 and the SARS2 NSP9 replicase 32 .…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Trasupporting
confidence: 90%
“…HCT intersections for nodes originally characterized as having a general role in RNA Pol II transcription, including TBP ( q -values: SARS1, 2e-10; SARS2, 6e-23; MERS, 3e-16), GTF2B/TFIIB ( q -values: SARS1, 7e-10; SARS2, 3e-23; MERS, 9e-14) and GTF2F1 ( q -values: SARS1, 2e-4; SARS2, 2e-13; MERS, 5e-5) were strong across all CoVs, and particularly noteworthy in the case of SARS2. In the case of GTF2B, these data are consistent with previous evidence identifying it as a specific target for orthomyxovirus 43 , and the herpes simplex 44 and hepatitis B 45 viruses. Moreover, a recent preprint has identified a high confidence interaction between GTF2F2 and the SARS2 NSP9 replicase 34 .…”
Section: Resultssupporting
confidence: 90%
“…MS data from S. cerevisiae and from human cells identify RNAPII, TFIIB, and TFIIF amongst the strongest interactors of Mediator (75,86), and these factors are necessary for reinitiation (25). Notably, another recent study revealed that human genes which require de novo RNAPII recruitment for induction of transcription depend on TFIIB availability (87). It is unclear how transcription factors modulate reinitiation, and in vivo evidence of reinitiation and scaffold complexes is lacking (32).…”
Section: Discussionmentioning
confidence: 99%